The interstitial response to renal injury: fibroblast-like cells show phenotypic changes and have reduced potential for erythropoietin gene expression. - Maxwell, P; Ferguson, D; Nicholls, L; Johnson, M; Ratcliffe, P (1997)
To define the potential for erythropoietin gene expression in injured kidneys, marker gene expression was examined in transgenic mice bearing a homologously recombined erythropoietin--simian virus 40 T antigen (Epo-TAg) transgene. Three types of renal injury were studied: ureteric obstruction, global ischemia following clamping of the renal pedicle, and focal needlestick injury. All modes of injury were associated with an expansion of the interstitial space, which contained an increased number of cells. Alterations observed in the interstitial fibroblast-like cells included an increased number and complexity of cellular processes, enhanced expression of contractile elements, particularly of the intermediate filament desmin, and reduced expression of ecto-5'-nucleotidase. Following each type of injury there was a focal or general reduction in the proportion of such cells that could be stimulated to express Epo-TAg. However, some positively staining cells were present even in severely injured regions and more could be recruited to express Epo-TAg by severe anemic or hypoxic stimulation, indicating that cells with the potential for erythropoietin gene expression were neither absent nor completely refractory to stimulation in these regions. In all injured kidneys, Epo-TAg expression was limited to the fibroblast-like population. Double labeling experiments showed that cells expressing Epo-TAg also expressed increased amounts of desmin, demonstrating that the myofibroblast features which develop in response to injury and the capacity for erythropoietin gene expression are not mutually exclusive.